The Last 40 Years of Orthognathic Surgery: A Bibliometric Analysis - Balel, Yunus (Journal of oral and maxillofacial surgery, 2023)
Bibliometric analyses provide information on the effectiveness, performance, trends, and various other characteristics of research by using mathematical and statistical analysis methods for data related to scientific publications. This study aims to determine the focus of studies in the field of orthognathic surgery, map it, and present the results in a simplified manner through a comprehensive bibliometric analysis of the relevant literature. In this bibliometric analysis study, orthognathic surgery publications from 1980 to 2022 were retrieved from the Web of Science Core Collection database. The independent variables were co-citations, while the outcome variables included cross-country collaboration analysis, keyword analysis, co-citation analysis, and cluster analysis of the co-citation network. Covariates were the number of publications, number of citations, year range, centrality value, and silhouette value. The bibliometric analysis was conducted using CiteSpace, VOSviewer, and R-Studio software. A total of 7,135 publications and 75,822 references were included in the analysis, and the annual growth rate of publications was 9.52%. The co-citation clustering analysis revealed that the orthognathic surgery literature was organized into 16 subject headings. Patient satisfaction was found to be the most widely published topic. The youngest clusters, representing new topics in the field, were virtual planning and examination of condylar changes after orthognathic surgery. Bibliometric analysis methods were used to evaluate the 40-year history of the orthognathic surgery literature. The analysis identified the most influential publications, the topics in which the literature is divided, and hot spots in the field. By conducting similar bibliometric research studies in the future, the progress and future direction of the literature can be monitored based on evidence.